Systematics of the endemic south-west African dung beetle genus Pachysoma Macleay (Scarabaedae : Scarabaeinae) - Scholtz, Clarke H. (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 2006.